2021
DOI: 10.3390/ijms22147460
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dihydromyricetin and Metabolites in Serum and Brain Associated with Acute Anti-Ethanol Intoxicating Effects in Mice

Abstract: Dihydromyricetin is a natural bioactive flavonoid with unique GABAA receptor activity with a putative mechanism of action to reduce the intoxication effects of ethanol. Although dihydromyricetin’s poor oral bioavailability limits clinical utility, the promise of this mechanism for the treatment of alcohol use disorder warrants further investigation into its specificity and druggable potential. These experiments investigated the bioavailability of dihydromyricetin in the brain and serum associated with acute an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It was demonstrated that DMY could protect rats against ethanol‐induced acute intoxication by affecting the related targets of γ‐Aminobutyric acid type A (GABAA) receptors (GABAARs) [111]. Furthermore, an investigation on the biotransformation of DMY related to the acute ethanol anti‐intoxication in mice demonstrated that 3 metabolites of DMY influenced the increased expression of GABAARs [99].…”
Section: Pharmacological Effects and Actions Mechanisms Of Dmymentioning
confidence: 99%
“…It was demonstrated that DMY could protect rats against ethanol‐induced acute intoxication by affecting the related targets of γ‐Aminobutyric acid type A (GABAA) receptors (GABAARs) [111]. Furthermore, an investigation on the biotransformation of DMY related to the acute ethanol anti‐intoxication in mice demonstrated that 3 metabolites of DMY influenced the increased expression of GABAARs [99].…”
Section: Pharmacological Effects and Actions Mechanisms Of Dmymentioning
confidence: 99%
“…Furthermore, dihydromyricetin had no adverse side effects on pregnant rats, which could make it a good candidate for prevention of foetal alcohol spectrum disorders [ 110 ]. More recently, dihydromyricetin was demonstrated to potentiate GABAergic activity, as shown in electrophysiology studies of α 5 β 3 γ 2 GABA A Rs expressed in Xenopus oocytes, although its metabolite 4- O -methyl-dihydromyricetin negatively modulates GABAergic activity [ 130 ]. In the case of the quercetin 5-dehydroxy-derivate fisetine ( Table 1 ), chronic treatment can delay or correct neuropathic hyperalgesia and allodynia in mice with type-1 diabetes; mechanistically, this effect may be associated with its antioxidant activity and spinal GABA A [ 73 ].…”
Section: Natural Products As Potential Gaba Modulatorsmentioning
confidence: 99%
“…In the present work, we investigated the solubility, activity, and Microcrystal electron diffraction (MicroED) 4,5 structure of salt formulations of the natural product dihydromyricetin (DHM), a brainpermeable flavonoid with high chemical similarity to a known in vitro tau inhibitor, EGCG 6 . DHM is a plant-derived polyphenol with antioxidant 7,8 and anti-inflammatory [9][10][11] activity and potential benefits in ameliorating dyslipidemia 7,9,12,13 and alcohol intoxication 14,15 . The CNS effects of DHM are attributed to increased GABAergic transmission and synaptic functioning, reduced neuroinflammation, and restoration of redox imbalances in neurons through improved mitochondrial function.…”
Section: Introductionmentioning
confidence: 99%
“…While hydrophobic character of DHM allows for permeability to the CNS, poor water solubility impedes dosing and intestinal absorption. [19][20][21][22] Water-soluble formulations of DHM could overcome dosing issues by enabling delivery of higher dosage concentrations to enable increased absorption.…”
Section: Introductionmentioning
confidence: 99%